Identifikasi Kerusakan Bangunan dan Fungsi Infrastruktur Akibat Banjir Citarum di Wilayah Kabupaten Bandung - Setiadi, Harri A (Puslitbang Kebijakan dan Penerapan Teknologi (PKPT), Kementerian PUPR, 2013)
Repetitive flood occurrence with rising escalation and intensity influenced community who lived around Citarum watershed. Tangible impacts which directly influence community are building damage and infrastructure disruption. This study identifies the impacts of Citarum flood on building damage and infrastructure functionality. The study uses qualitative approach and takes 2010 Citarum flood disaster case study in Bandung Regency. The research is conducted on human settlements along the river bank and the adjacent areas. Principal tool for collecting primary data are observation and interview. Ecological perspective is used to identify the flood along Citarum river banks and adjacent areas, failure mechanism of building component concepts is used to identify flood impacts on building damage, and public infrastructure concepts is used to identify flood impacts on infrastructure disruption. The research results are presented in three sections according to the above identifications.